MEMAHAMI HADIS-HADIS AF’ÂL AL RASÛL DAN TANAWWU’ AL IBÂDAH - Hafizzullah Hafizzullah (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2016)
The life of Prophet Muhammad is a great example of Muslims, especially his actions. Yet, many Muslims do not fully comprehend the deeds of the Prophet Muhammad. They assume that every Prophet’s actions are an obligation or an option to follow. Though the careful studies on the issue have elaborated and come to the conclusion that not every that Prophet Muhammad’s action have to follow. The Islamic scholars have distributed the diversity of prophet actions and explained the content of the law, with the level of obligaion, ibahah (permition) or or a good example to follow from the actions of the Prophet Muhammad.